Application of the concept of a renewable energy based‐polygeneration system for sustainable thermal desalination process—A thermodynamics' perspective. (29th January 2020) - Luqman, Muhammad; Ghiat, Ikhlas; Maroof, Moiz; Lahlou, Fatima‐Zahra; Bicer, Yusuf; Al‐Ansari, Tareq
Summary: Fossil fuel‐powered thermal desalination processes have many harmful environmental effects including greenhouse gas (GHG) emissions and high‐salinity brine discharge resulting in biological damages, in addition to energy losses because of the high temperatures of the streams leaving the desalination unit. In this study, a solar energy‐based polygeneration approach has been proposed to address these issues. In the proposed system, concentrated solar parabolic trough technology is used to drive a multi‐stage flash (MSF) desalination unit for production of fresh water. To recover the waste heat carried by the produced clean water, an organic Rankine cycle is integrated to produce electricity. In addition, to recover the waste heat carried by brine, an absorption cooling system is employed to provide cooling. In order to mitigate the effects of high‐salinity brine, a pressure retarded osmosis (PRO) unit is installed, which reduces the salinity of the discharge and produces additional electrical energy. To ensure stable nighttime operations, a thermal energy storage (TES) system is also added to the system. A comprehensive thermodynamic analysis is conducted through mass, energy, and entropy, as well as exergy balances along with energetic and exergetic efficiencies to assess the overall performance of the system. The attained results show that at reference conditions with an overall parabolic trough collectors (PTCs) area of 100 000 m 2, the system produces 583.3 kW of electricity, approximately 4284 kW of cooling, and 1140 m 3 of freshwater daily. Furthermore, the effects of changing operational conditions on the overall performance of the system are investigated. At design conditions, the overall energetic and exergetic efficiencies of the system are found to be 34.54% and 14.55%, respectively. Abstract : This study proposes a way – based on the concept ofpolygeneration – to mitigate the environmentally harmful effects of thermal desalination. The proposed system replaces fossil fuels with solar energy, integrates ORC and ACS to recover low‐grade thermal energy, a PRO sub‐system tomitigate the harmful effects of high concentration brine discharge to sea and aTES unit to make the system resilient against varying weather conditions. Detailed thermodynamic analysis demonstrates that the systemoperates stably with varying inputs and environmental conditions.